Synthesis of diboride powders by dry route
A dry route method for producing titanium diboride using controlled oxide powders and reducing metals under specific conditions addresses the inefficiencies of existing methods, achieving high-purity, finely divided titanium diboride with low environmental impact and simplified extraction.
Patent Information
- Application Number
- JP2024541678
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-11
- Filing Date
- 2023-01-10
- Publication Date
- 2025-01-09
AI Technical Summary
Existing methods for producing titanium diboride suffer from low material efficiency, high energy consumption, environmental and health hazards due to CO emission, and the production of fine or ultrafine powders that are expensive and difficult to separate, while also requiring complex industrial processes.
A method involving a dry route using specific oxide powders of titanium, boron oxide, and a reducing metal under controlled temperature and gas flow conditions to produce titanium diboride with high purity and controlled particle size, minimizing CO release and simplifying the extraction process.
The method achieves a high-purity, finely divided titanium diboride powder with controlled particle size and low environmental impact, enabling efficient production and easy separation without complex processes, suitable for various applications.
Smart Images

Figure 2025500665000003 
Figure 2025500665000004 
Figure 2025500665000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a new method for the preparation or synthesis of diborides of elements of Group 4 of the periodic table, in particular titanium diboride. [Background technology]
[0002] Diborides of Group 4 elements of the periodic table, particularly titanium diboride, zirconium diboride, or hafnium diboride, have many advantages, including high refractoriness, high toughness, and good chemical inertia.
[0003] In particular, titanium diboride has a low density (approximately 4.5 g / cm 3 ), a ceramic material with high hardness, high thermal conductivity and low electrical resistivity, which makes it an interesting material for various applications, such as refractory applications where thermal and high electrical conductivity are advantageous, in particular heat exchangers, coatings or even compositions for anodes or cathodes of electrolytic reactors, or even membranes in certain temperature applications or in highly aggressive chemical media, and crucibles for melting metals, in particular for melting non-ferrous metals, or cutting tools or shielding or wear-resistant coatings, etc.
[0004] All these applications explain why the demand for this material is very high and currently increasing.
[0005] Diborides do not exist in the natural state. Titanium diboride can in particular be obtained, for example, by direct reaction of titanium (or its oxide or hydride) with elemental boron at 1000° C. or by carbothermal reduction of titanium oxide with boron oxide. In the latter case, the reaction consists of reacting a mixture of powders at temperatures above 1500° C. according to the following simplified reaction: TiO2(s)+B2O3(s)+5C(s) → TiB2(s)+5CO(g) (1)
[0006] However, this method has a theoretical material efficiency of about 30%.
[0007] Another less well known method consists in substituting boron carbide, specifically boron oxide powder, as shown in the following reaction balance: 2TiO2+B4C+3C → 2TiB2+4CO (2)
[0008] The advantage of such a reaction is its relatively high theoretical material efficiency (55.4%) and therefore the relatively low emission of carbon monoxide, but it has the disadvantage of requiring reaction temperatures in excess of 1600° C. and produces non-negligible amounts of CO in gaseous form, which poses health, safety and environmental problems.
[0009] Furthermore, the methods for producing this material become increasingly expensive and energy intensive as the desired final powder of titanium diboride becomes relatively fine (typically having a median diameter of 5 to 50 micrometers) or ultrafine (median diameter less than 5 micrometers).
[0010] Another known solution consists of metallothermal reduction using elements in metallic form, such as Al, Si, Mg, Ca, etc., instead of carbon. The exothermic reaction associated with the use of these reagents produces diborides by self-propagating high-temperature synthesis (SHS), but leads to incomplete conversion of the reagents, traditionally requiring a second reaction, typically with boric acid H3BO3, to obtain a relatively good conversion to the diborides.
[0011] Another solution also consists of synthesis in a mixture of salts in the molten state or in solution. Thus, published patent application WO 2020 / 073767 from Wuhan University of Science and Technology proposes a relatively cheap and relatively environmentally friendly method for producing TiB2 or (Zr,Hf)B2 layers from a mixture containing a source of titanium (or zirconium or hafnium), a source of boron, a reducing agent (Si or Al in metallic form) and an alkali salt. The alkali salt may be selected from hydrates, silicates or carbonates of sodium, lithium or potassium, thereby forming a liquid phase at low temperatures. However, the addition of silicates results in reactants that are difficult to separate. The addition of one or more carbonates causes the problem of CO2 release due to the decomposition of the carbonates during the synthesis reaction. Summary of the Invention [Problem to be solved by the invention]
[0012] The object of the present invention is therefore to improve the above mentioned synthesis method, thereby obtaining a diboride powder of an element of group 4 of the periodic table, in particular TiB2, which is such that: - fine, i.e. powders typically having a median diameter between 0.5 microns and 50 microns (0.5 μm and 5 μm); - of relatively high purity, i.e. with an elemental mass content of less than 5%, preferably less than 3% or 2% or less as a sum of the following contaminants: oxygen (O), sulfur (S), carbon (C), nitrogen (N), iron (Fe), phosphorus (P), silicon (Si) and / or aluminium (Al), in particular in metallic form, cobalt (CO), nickel (Ni), alkali metals (Li+Na+K+Rb+Cs), alkaline earth metals (Be+Mg+Ca+Sr+Ba); At the same time, - Satisfactory material efficiency, e.g. at least 20%; - the diboride powder can be easily extracted from the reaction product; - very low, preferably no, CO or CO2 emissions; and - Do not rely on overly complicated industrial processes for the synthesis of powders. [Means for solving the problem]
[0013] In particular, according to a first aspect, the invention relates to an alternative method for producing diboride powders of elements of group 4 of the periodic table, in particular titanium diboride TiB2, at temperatures below 1500° C., preferably below 1400° C., preferably below 1300° C. or even below 1200° C., and for this purpose without the use of solvents or surfactants, thanks to an appropriate selection of the starting powders.
[0014] More specifically, the present invention relates to a method for producing a diboride powder MB2, where M is a chemical element belonging to group 4 of the periodic table, by reducing an oxide MO2 of said element M, said method comprising the following steps: - The following: (a) a powder having a mass content of said oxide MO2 of at least 95%; and (b) a powder containing boron oxide or a precursor of boron oxide, the boron content of which, expressed as B2O3, is at least 30%; and (c) a metal powder of at least one reducing element R, where R is selected from Al, Si, Ti, Zr, Hf, Y, Sc, lanthanides; and (d) an oxide powder of an alkali element A having a mass content of A0 of at least 70%; in the respective proportions, preferably corresponding thereto, leading to the following reaction balance, expressed according to MO2, B2O3, R, and A2O as above, and preferably consisting of: MO2+B2O3+yR+xA2O → MB2+A 2x R y O 5+x (3) - heating said mixture in a vessel under a stream of noble gas at a temperature above 600°C and below 1500°C, thereby obtaining compound MB2; wherein the raw material mixture has the following characteristics: - the median particle size of the powder containing the oxide MO2 is 1 to 100 microns (1 to 100 μm); and - the powder containing boron oxide or a boron oxide precursor has a median particle size of between 5 and 200 microns (5-200 μm); and - x is greater than or equal to 1, - y is greater than 0.5.
[0015] According to preferred but non-limiting embodiments of the present invention, which may be combined with one another where appropriate, are the following: the total mass of the powder with a mass content of said oxide MO2 of at least 95%, the powder comprising boron oxide or a boron oxide precursor, the metallic powder of at least one reducing element R and the oxide powder of an alkali element A represents more than 80% by weight, or even more than 90% by weight, or even more than 95% by weight of said mixture. The powder, whose mass content of oxide MO2 is at least 95%, comprises several MO2 oxides, in particular a mixture of TiO2, ZrO2 and / or HfO2. said powder with a mass content of oxide MO2 of at least 95% comprises a mixed oxide comprising at least two different elements M, M being selected from Ti, Zr and Hf; the powder is made of an oxide MO2, preferably titanium oxide; the powder comprises boron oxide or a precursor of boron oxide, expressed as B2O3, the boron mass content of which is at least 40%. The metal powder comprises at least one reducing element R selected from the elements aluminum (Al) and / or silicon (Si). the powder of an oxide of an alkali element A, preferably sodium oxide (Na2O), having a mass content of A2O which is at least 80%; the hydroxyl (OH) content of the oxide powder of the alkali element A, calculated in the form of the mass of OH relative to the mass A0, is preferably less than 30%, more preferably less than 20%, or even less than 10%, or even less than 5%, or even essentially zero. - The flow rate of the gas in the above vessel is 1 m 3 The flow rate is 0.5 to 10 L / min. The powder containing the oxide MO2 has a median particle size of 30 to 100 μm, and more preferably 30 to 50 μm. The powder containing boron oxide has a median particle size of 10 to 100 microns (10 to 100 μm). the total content of said mixture of alkali metal oxide raw materials, calculated in the form of A2O, is equal to or greater than the amount required for said reaction (3), whereby x is greater than 1, preferably x is between 1.5 and 5, more preferably x is between 1.5 and 2. the residual mass content H2 of said raw material mixture, measured at atmospheric pressure and at a temperature of 400°C, is less than 5%. - y is greater than 1.
[0016] According to one possible embodiment, the raw material mixture comprises an oxide powder MO2 of a first chemical element M belonging to group 4b of the periodic table and a second oxide powder MO2 of a second chemical element M belonging to group 4b of the periodic table different from the first element, where M is selected from Ti, Zr or HfO2.
[0017] According to another embodiment, which can be combined with the previous one, the raw material mixture comprises at least one oxide powder MO2, where M is a mixture of at least two, preferably two, chemical elements belonging to group 4b of the periodic table.
[0018] As will be explained in more detail below, such a combination of parameters advantageously allows for obtaining a fine powder of MB2 diboride of high purity with satisfactory material efficiency using a process that emits little or no CO or CO2, and allows for said diboride powder to be readily extracted without the use of overly industrially complex powder synthesis processes.
[0019] The respective proportions leading to the reduction of the oxide of element M to the diboride of element M are substantially stoichiometric amounts of the various reagents mentioned above (a)-(d) leading to reaction balance (3).
[0020] For example, when using lithium oxide precursors of the Na2B4O7 type, 1 mole of B2O3 in reaction (3) corresponds to the addition of 1 / 2 mole of the reagent Na2B4O7.
[0021] Thus, when using boron oxide B2O3, the reaction balance (3) can be written as follows: MO2+B2O3+R+xA2O → MB2+A 2x RO 5+x
[0022] When using the boron oxide precursor Na2B4O7, reaction balance (3) can be written as follows: MO2+B2O3+yR+xA2O → MB2+A 2x R y O 5+x where M=Ti, A=Na, R=Al, x=5 / 3, and y=10 / 3.
[0023] In particular, unlike synthesis methods using molten salts or in solution in a solvent, especially water, the method according to the invention by the dry route, in particular by using an oxide powder of a weakly hydroxide or non-hydroxide alkali element A, rather than using alkali salts in solution, as described, for example, in WO2020073767, advantageously allows an optimal reaction, i.e. a reaction with a maximum material balance, while allowing an easy separation of the diboride powder of element M after synthesis in a vessel.
[0024] According to further preferred embodiments of the invention, which may be combined with one another where appropriate, there are: The boron oxide precursors are chosen from compounds in which boron is in a non-carbide, non-metallic form and in a form other than a salt, and in particular other than a halide, such as boron nitride. - the boron oxide is selected from B2O3, sodium metaborate with the chemical formula NaBO2, anhydrous borax with the formula Na2B4O7, or other borate salts such as natural borax with the formula Na2B4O7·10H2O, tincalconite with the formula Na2B4O7·5H2O, kernite with the formula Na2B4O7·4H2O, ulexite with the formula NaCaB5O9·8H2O, provertite with the formula NaCaB5O9·5H2O, sassolite with the formula H3BO3, etc. Preferably, the boron oxide is selected from sodium metaborate with formula NaBO2, anhydrous borax with formula Na2B4O7, or other borate salts, such as natural borax with formula Na2B4O7·10H2O, tincalconite with formula Na2B4O7·5H2O, kernite with formula Na2B4O7·4H2O, ulexite with formula NaCaB5O9·8H2O, provertite with formula NaCaB5O9·5H2O, etc.; The powder containing boron oxide is an anhydrous alkaline borate powder, preferably an anhydrous sodium borate powder. - The median particle diameter (D 50 ) is greater than 7 μm, preferably greater than or equal to 10 μm and / or less than 50 μm, or even less than 30 μm. - diameter D of the particles of the powder containing the oxide MO2 90 is less than 100 micrometers, preferably less than 80 micrometers, preferably 50 micrometers or less, more preferably 40 micrometers or less; - The median particle diameter (D 50 ) is greater than 10 μm, preferably greater than or equal to 30 μm and / or less than 100 μm, or even less than 50 μm. - The median particle diameter (D 50 ) is greater than 10 μm, preferably greater than or equal to 30 μm, and / or preferably less than 100 μm, preferably less than 50 μm, or even less than 30 μm. The oxide powder of the alkali element A is a powder in the form of granules having a size greater than 30 μm and / or less than 100 μm. the ratio of the median particle size of the powder comprising boron oxide to the median particle size of the metal oxide powder M is less than 30, preferably less than or equal to 10, and / or greater than 5, preferably greater than 2. This ratio makes it possible to optimize the conversion of element M to diboride. the ratio of the median particle size of the powder comprising said boron oxide to the median particle size of the powder comprising said oxide M2 is less than 10 and / or greater than 1. A is the element Na. R is the element Al and / or Si M is the element Ti, A is the element Na and R is the elements Al and / or Si. The powder comprising the oxide MO2 is a titanium oxide powder, preferably a rutile or anatase powder, even more preferably rutile. - the mass content of SiO2+Al2O3+Fe2O3+Na2O+K2O+CaO+MgO in the powder containing an oxide MO2, preferably titanium oxide, is less than 5%. In particular, the mass content of SiO2 in the powder containing an oxide MO2, preferably titanium oxide, is preferably less than or equal to 2%. The mass content of Al2O3 in said powder containing an oxide MO2, preferably titanium oxide, is preferably less than or equal to 2%. Preferably, the mass content of Fe2O3+Na2O+K2O+CaO+MgO in said powder containing an oxide MO2, preferably titanium oxide, is preferably less than or equal to 1%. Preferably, the mass content of the sum of the element carbon (C)+nitrogen (N) in said powder containing an oxide MO2, preferably titanium oxide, is preferably less than or equal to 1%, preferably less than or equal to 0.5%. the mass content of elemental silicon (Si), expressed in the form of SiO2, in the raw mixture before the reaction, apart from the reducible metal powder R which may contain this element, in particular if it is silicon powder, is preferably less than 2%, preferably less than 1%. - The raw materials were pre-dried at temperatures between room temperature and 150°C. the synthesis temperature, i.e. the heating temperature in said vessel, is greater than 700°C, preferably greater than 800°C, and / or less than 1400°C, preferably less than 1300°C, more preferably less than 1200°C; - The pressure in the vessel is kept substantially constant, for example between 0.5 and 1.5 bar, even more preferably the vessel is at atmospheric pressure (1 bar). The gas sweeping the vessel is preferably a noble gas, for example argon or helium, preferably argon. Preferably, the gas sweeping the vessel, preferably a noble gas, is introduced into the vessel in contact with the raw material mixture. The flow rate is preferably 1000 ml / m 3 of the vessel. 3 0.5 to 5 L / min per 1 m of container, preferably 3 0.5 to 3 L / min per 1 m of container, preferably 3 A flow rate of 0.5-2 L / min per minute is preferred. Too low a flow rate can lead to incomplete reaction and, more particularly, to the presence of undesirable residues in the final powder of diboride MB2. - The flow rate of the inert non-oxidizing gas for washing is 1 m 3 A range of 0.005 to 1 L / min per 1 kW of heating power of the vessel is particularly optimal, and preferably 1 m of the vessel 3 The average heating power is 0.01 to 0.5 min per kW of heating power of the vessel.
[0025] After reaction, finely divided raw diboride powder of Group 4 of the Periodic Table can be easily extracted from the crude mixture obtained from the vessel after the heating step.
[0026] According to one possible embodiment, a sieving operation, typically to a diameter of 100 μm, preferably to a diameter of 50 μm, or even light grinding or vibration, makes it possible to remove the agglomerates and to separate the raw powder of diboride of element M. A suspension is produced by adding a solvent, preferably deionized water, to the previously ground crude mixture in a mass ratio of 1 part crude mixture to at least 20 parts solvent, preferably 50 parts solvent. The suspension is filtered to an optimal size, typically less than 30 μm, preferably less than 20 μm, thereby making it possible to pass the liquid containing very fine residues of the other products of reaction (3). The filtered distillate, consisting of the powder of diboride of element M, is then calcined or dried, preferably in air, at a temperature above 80° C., preferably above 100° C., and / or preferably below 300° C., preferably below 200° C., preferably below 150° C.
[0027] According to one possible embodiment, the liquid obtained from the filtration of the abovementioned suspension, which contains the products of reaction (3), apart from the diboride powder of element M, is thermally treated in the presence of water and a basic solution, thereby forming a hydrate of element R and an alkali hydroxide. This embodiment is represented by the formula A 2x R y O 5+x Preferably, this possibility is particularly advantageous when the element R is Al and the alkali A is sodium.
[0028] The invention also relates to a powder of a diboride of an element M of group 4 of the periodic table, and in particular to a powder of titanium diboride TiB2, obtainable according to the process described above.
[0029] The powder comprises greater than 95% by weight of the compound MB2, where M is selected from Ti, Zr, and Hf. The powder has a median particle size of 0.5 to 50 microns (0.5-50 μm), and further comprises the following weight percentages: - elemental oxygen (O): less than 1.3%, preferably less than 1.2%, preferably less than 1% or even less than 0.5%; - elemental carbon (C): less than 0.5%, preferably less than 0.1%; - elemental nitrogen (N): less than 0.5%, preferably less than 0.1%; - elemental sulfur (S): less than 400 ppm, preferably less than 300 ppm, or even less than 150 ppm, or even less than 100 ppm or less than 50 ppm; - elemental iron (Fe): less than 0.45%, preferably less than 0.4%; - elemental nickel (Ni): less than 0.4%, preferably less than 0.2%, or even less than 0.1%; - elemental cobalt (CO): less than 0.4%, preferably less than 0.2%, or even less than 0.1%; - the total elements of alkali metals Li+Na+K+RB+Cs: less than 1%, preferably less than 0.5%; - the total element of alkaline earth metals (Be+Mg+Ca+Sr+Ba): less than 1%, preferably less than 0.5%, or even less than 0.25%; - the content of element R in metallic form: less than 2%, preferably less than 1%, more preferably less than 0.5%, R being preferably different from M, R being at least one element selected from Al, Si, Ti, Zr, Hf, Y, Sc, the lanthanides; The sum of other elements is less than 2%, preferably less than 1%.
[0030] Preferably, the sum of the elements oxygen (O)+nitrogen (N)+carbon (C) in the diboride powder of element M is less than 1.5%, or even less than or equal to 1.2%.
[0031] Preferably, the mass content of silicon (Si) in metallic form in the diboride powder of element M is less than 0.1%.
[0032] Preferably, the mass content of aluminum (Al) in metallic form of the diboride powder of element M is less than 2%, preferably less than 1%, more preferably less than 0.5%.
[0033] Preferably, the final powder of MB2 according to the invention does not contain any crystallized phases, such as M2O3, M3B4, etc., as determined (detectable) by X-ray diffraction. Preferably, said powder contains only crystalline phases of MB2, as determined (detectable) by X-ray diffraction.
[0034] Preferably, the raw powder, i.e. the powder after extraction of the crude mixture from the container after the heating step, is used, in particular the powder of formula A 2x R y O 5+x The ratio of equivalent diameters of the particles (D 90 -D 10 ) / D 50 is less than 2, preferably less than 1.5, more preferably less than 1.2, or even less than 1.5. 10 , D 50 , and D 90 are the diameters corresponding to the 10%, 50% and 90% percentages, respectively, on the cumulative curve of the particle size distribution by volume, sorted in increasing order, of said powder.
[0035] In the case where M=Ti, the mass content of the element Ti is preferably greater than 68% and / or less than 72%, the mass content of the element boron is preferably greater than 29% and / or less than 33%. Preferably, the mass content of the element phosphorus is less than 0.3%, preferably less than 0.2% or even less than 0.1%.
[0036] Such diboride powders of an element M of group 4 of the periodic table with regular particle size, in particular high purity and fine TiB2 powder, make it possible to obtain sintered ceramic bodies with a total porosity of less than 7% by volume by sintering without the addition of transition metals, such as Ni, Fe or CO, which may lead to the undesired formation of secondary metal borides from these metals.
[0037] Such powders make it possible to obtain sintered ceramic bodies in the form of parts, at least one dimension of which, preferably all overall dimensions, are greater than 5 cm, or even greater than 10 cm, have a total porosity of less than 7%, have a very narrow pore size distribution, do not deform during sintering, and are free of shrinkage cracks.
[0038] Preferably, M is Ti.
[0039] And said diboride powder of element M of group 4 of the periodic table is a powder of the compound TiB2, which further comprises one or more of the following percentages by weight: Titanium (Ti): more than 68% and / or less than 72%; Boron (B): more than 29% and / or less than 33%; oxygen (O): less than 1%, preferably less than 0.5%, or sulfur (S): less than 400 ppm, less than 300 ppm, less than 100 ppm, preferably less than 50 ppm; - preferably phosphorus (P): less than 0.3%, preferably less than 0.2%, preferably less than 0.1%.
[0040] And said diboride powder of element M of group 4 of the periodic table is a powder TiB2 having a chemical composition comprising the following element mass percentages: Titanium (Ti): more than 68% and / or less than 72%; Boron (B): more than 29% and / or less than 33%; - preferably less than 0.3% phosphorus (P); - Metallic aluminum: less than 2% - Metallic silicon: less than 1%.
[0041] The equivalent diameter ratio of the particles of MB2 powder (D 90 -D 10 ) / D 50 is advantageously less than 1.5, more preferably less than 1.2, or even equal to or less than 1.0.
[0042] The present invention also relates to a mixture comprising 90-99.9% by weight of a diboride of an element M of group 4 of the periodic table and 0.1-10% by weight of one or more sintered powders, or even to a mixture consisting of a powder of a diboride of an element M of group 4 of the periodic table according to the invention, preferably a powder of titanium diboride (TiB2), and 0.1-10% by weight of one or more sintered powders selected from aluminium diboride, magnesium diboride, zirconium diboride, tungsten pentaboride, calcium hexaboride, preferably silicon hexaboride, optionally zirconium diboride powders in the case of M=Ti or Hf, the purity of which is greater than 95% by weight, preferably greater than 98% by weight. A purity of more than 95% by weight is the purity of said phase or of the most stable main compound: for example, in the case of aluminum diboride powder, it is more than 95% by weight of AlB2, or in the case of tungsten pentaboride powder, it contains more than 95% by weight of W2B5.
[0043] The invention likewise relates to a method for producing a sintered ceramic body, comprising the steps of: (a) generating a starting feedstock comprising: a diboride powder of an element M of group 4 of the periodic table, preferably a diboride powder of TiB2 and / or (Zr,Hf)B2 obtainable by the method according to the invention, more preferably a diboride powder of TiB2, or a mixture of powders as described above comprising said powders and one or more of the sintered powders described above. - aqueous solvents, in particular deionized water, - preferably a molding additive, (b) forming the feedstock material into the shape of a preform, preferably by pressing; (c) Removal from the mold after solidification or drying; (d) optionally drying the preform, preferably to a residual moisture content of 0-0.5 wt.%; (e) Loading into a furnace and firing the preform under an inert atmosphere, preferably under an argon atmosphere or under vacuum, preferably at a temperature between 1600° C. and 2200° C.
[0044] The invention also relates to the ceramic sintered bodies thus obtained and to the use of the ceramic sintered bodies obtained by the process as described above, in particular as membranes, barrier or wear-resistant coatings, coverings or refractory blocks, anode or cathode coatings or blocks, in particular for the filtration of liquids or gases, in electrolytic reactors, heat exchangers, metal melting crucibles, in particular for non-ferrous metals, cutting tools, or in whole or in part.
[0045] definition
[0046] The following indications and definitions are provided in connection with the foregoing description of the invention: - In this specification, unless otherwise stated, all percentages are given by weight on a dry basis. the term "boron oxide" is understood to mean any oxide comprising boron and oxygen, optionally containing at least one other element, in particular an element selected from Na, Ca, said oxide optionally being hydrated; boron oxide precursor is understood here to mean a powder comprising the element boron (B), which is oxidized to give the reagent B2O3 present in the chemical formula of reaction (3), for example by oxidation, for example by heating in an oxidizing gas, preferably in air, to a temperature of less than 600°C or by contacting with an oxide present in the raw material mixture. - The material efficiency is calculated by dividing the mass of the resulting untreated diboride powder of element M by the mass of the dry mixture of reagent powders (moisture content less than 5%) before heat treatment. - "raw mixture" is understood to mean the mixture obtained directly at the outlet of the vessel after the thermal reaction of the raw mixture and before further processing to extract the raw diboride powder of element M, for example by sieving or slight grinding. - the median diameter (or median "size") of the particles constituting a powder is given in the sense of the present invention by characterizing the particle size distribution, in particular by means of a laser granulometer. The characterization of the particle size distribution is conventionally carried out by means of a laser granulometer according to the standard ISO 13320-1. The laser granulometer can be, for example, a Partica LA-950 from HORIBA. For the purposes of this specification, unless otherwise stated, the median particle diameter denotes the particle diameter below which 50% by weight of the population is found, respectively. The "median diameter" or "median size" of a collection of particles, in particular of a collection of powders, is given by the D 50 Percentiles D of grains or powders of particles are called percentiles, i.e. sizes that divide particles into first and second populations of equal volume, which contain only particles having sizes larger or smaller than the median diameter, respectively. 10 and D. 90 It is also possible to determine the diameters corresponding to the 10% and 90% percentages, respectively, on the cumulative distribution curve of particle sizes by volume sorted in increasing order. - The elemental chemical content may be determined according to the ISO 21068:2008 standard.
[0047] In particular, the following mass contents are as follows: - O, N, C, S are measured by LECO® brand analyzers; - Si, Al, CO, Ni, Alkali (Li+Na+K+RB+Cs), Alkaline Earth (Be+Mg+Ca+Sr+Ba), Fe, P can be determined by ICP (Inductively Coupled Plasma), The M element (especially Ti, Zr, Hf) content is preferably determined by ICP. The metallic form of aluminium or the metallic form of silicon, or the compound MB2, can be determined by X-ray diffraction. - The hydroxyl (OH) content of the oxide powder of the alkali element A can be measured by pH measurement. - Actual powder density is measured by helium pycnometry, for example using a MicrOmeritics AccuPyc1330 instrument. The total porosity of a ceramic body is the ratio, expressed as a percentage, of the bulk density, measured, for example, according to ISO 18754, to the absolute density, measured, for example, according to ISO 5018.
[0048] Unless otherwise specified, all percentages herein are percentages by weight. [Brief description of the drawings]
[0049] [Figure 1] FIG. 1 shows the untreated powder according to Example 2 of the present invention.
[0050] [Diagram 2] FIG. 2 shows the untreated powder according to Comparative Example 1.
[0051] [Diagram 3] FIG. 3 shows the untreated powder of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0052] Detailed Description
[0053] The invention and its advantages will be better understood from the detailed description set forth below. Of course, the invention is not limited to any of the aspects described below.
[0054] The mixture of starting materials includes: a powder comprising an oxide MO2 (for example a powder of titanium oxide, preferably a rutile or anatase powder), the mass content of MO2 being at least 95%; and - a powder containing boron oxide or a boron oxide precursor, the boron content, expressed as B2O3, being at least 30%; - metallic powders of reducing elements R chosen from Al, Si, Ti, Zr, Hf, Y, Sc and the lanthanides, mixtures thereof or alloys thereof, the mass content of elements other than Al, Si, Ti, Zr, Hf, Y, Sc and the lanthanides being less than 1%, preferably less than 0.5%, such as powders of the elements aluminium (Al) and / or silicon (Si), and a powder of an oxide of an alkali element A, the mass content of which is at least 70%, preferably at least 80%, preferably at least 90%, preferably at least 95%, preferably at least 98%, more preferably a powder of sodium oxide (NaO) of a purity of at least 99% or higher.
[0055] It is carried out under conditions standard to those skilled in the art. This step of producing a dry mixture allows for intimate contact of the particles. According to one possible embodiment, it is carried out in a ball mixer or in a tumbler mixer or in other equipment known to those skilled in the art. A prior co-grinding can be carried out, if necessary, to adjust the particle size of the starting materials.
[0056] If necessary, certain raw materials, such as borate or alkali element oxide powders, may be dried or calcined, thereby reducing their H2O or hydroxyl content. In the case of starting materials such as natural borax of formula Na2B4O7·10H2O (also in the form Na2B4O5(OH)4·8H2O), tincalconite of formula Na2B4O7·5H2O (also in the form Na2B4O5(OH)4·3H2O), kernite of formula Na2B4O7·4H2O (also in the form Na2B4O6(OH)2·3H2O), ulexite of formula NaCaB5O9·8H2O (also in the form NaCaB5O6(OH)6·5H2O), provertite NaCaB5O9·5H2O (also in the form NaCaB5O7(OH)4·3H2O), etc., this treatment reduces the presence of H2O adsorbed on the surface of the powder, or hydrogen present in the form of OH hydroxyl. This makes it possible to improve the conversion of element M into diborides, so that the green powder of MB2 after synthesis also has a very low content of reducing metals in element R.
[0057] Preferably, the hydroxyl (OH) content provided by the raw material in reaction (3) is minimized to maximize the conversion to diboride MB2. In particular, the borates may be calcined, thereby dehydroxylating them. Even more preferably, the alkali element A oxide powder has a hydroxyl content, calculated by dividing its OH mass by the alkali metal A2O mass, which is less than 40%, preferably less than 30%, more preferably less than 20%, or even less than 10%, or even less than 5%, or substantially zero.
[0058] The median particle size or median diameter of the oxide particles of element M is 1 to 100 microns (1 to 100 μm), preferably 7 to 80 microns (7 to 80 μm). The particles containing boron oxide, the metal particles of the reducing element R, and the oxide particles of the alkali element A are preferably 30 to 100 microns (30 to 100 μm), preferably 30 to 80 microns (30 to 80 μm).
[0059] Preferably, the median size ratio of the particles comprising boron oxide to those of the oxide of element M is 1-10.
[0060] Preferably, the mixture according to the invention comprises, by weight, 20-25% of an oxide of element M, 25-40% of a powder containing boron oxide or a boron oxide precursor, 20-30% of a metallic powder of a reducing element R, and 15-25% of an oxide powder of an alkali element A. In particular, when element M is Ti and A is Na, the mixture according to the invention comprises, by weight, 20-25% of titanium oxide, 25-35% of a powder containing boron oxide or a boron oxide precursor, preferably containing sodium borate, 20-30% of a metallic powder of a reducing element R, preferably Al and / or Si, and 15-25% of sodium oxide powder.
[0061] The total content of alkali oxides, calculated in the form A2O, in said raw mixture is equal to or greater than the stoichiometric amount required for said reaction (3), and is preferably less than 10%, or even less than 5%.
[0062] The mixture is dried, preferably in air, preferably at a temperature above 40° C., more preferably above 100° C., thereby obtaining a mixture, said mixture of raw materials having a residual moisture content, i.e. a residual mass content of HO measured by a moisture meter well known to the person skilled in the art, of less than 5%, preferably less than 2%, even more preferably less than 1%.
[0063] The mixture is placed in an inert crucible, preferably of diboride of element M or even of alumina, preferably of alumina coated with diboride of element M, for example in an induction furnace. The loose density of the mixture before heat treatment, measured according to the ASTM D7481-18 standard, is preferably greater than 0.1 times, or greater than 0.2 times, and / or preferably less than 0.5 times, less than 0.3 times, the density of MB2.
[0064] The temperature increase is preferably carried out up to at least one temperature higher than the melting point of the metal of element R selected from Al, Si, Ti, Zr, Hf, Y, Sc and the lanthanides, their mixtures or alloys, with inclusion of elements other than Al, Si, Ti, Zr, Hf, Y, Sc and the lanthanides, preferably higher than 600° C., preferably higher than 700° C., preferably higher than 800° C. and lower than 1500° C., preferably lower than 1300° C., in a non-oxidizing atmosphere, preferably under a flow of noble gas, in particular under a flow of argon, in order not to oxidize the powder of metal reducing agent R.
[0065] Preferably, the non-oxidizing gas sweep is performed for a period of time typically of 1 m 3 0.5 to 5 L / min per m, preferably 0.5 to 3 L / min per m 3 , more preferably 0.5 to 2 L / min / m 3 It is carried out at a flow rate of .
[0066] Preferably, the temperature increase is less than 20° C. / min, preferably less than 10° C. / min, preferably less than 5° C. / min, or even less than 3° C. / min. This temperature increase gradient, as well as the duration of the plateau, can be adjusted as a function of the mixing volume and the reactor power. In particular, such a temperature increase range facilitates a relatively good control of the exothermic effect due to the synthesis reaction of the powder according to the invention.
[0067] Preferably, the plateau at maximum temperature is at least 1 hour, preferably at least 2 hours.
[0068] Preferably, an intermediate plateau is performed between 600°C and 1000°C and / or a relatively low gradient, typically at least two times lower, is performed after 600°C, thereby preventing removal of the mixture and promoting reaction between the particles.
[0069] Cooling may be free or forced, preferably following a negative gradient of less than 20° C. / min.
[0070] The resulting raw material mixture typically has a particle size of 10 to 100 micrometers.
[0071] A sieving operation, typically to a diameter of 100 micrometers, preferably to a diameter of 80 micrometers, preferably to a diameter of 50 micrometers, or even a light grinding or vibration, makes it possible to remove the agglomerates and to separate the raw powder of the diboride of element M.
[0072] According to one possible embodiment, a sieving operation, or even light grinding or vibration, makes it possible to remove the agglomerates and to separate the powder of diboride of element M. The suspension is carried out by adding a solvent, preferably deionized water, to the previously ground crude mixture in a mass ratio of 1 part crude mixture to at least 20 parts solvent, preferably 50 parts solvent. The suspension is filtered to an optimum size, typically less than 30 μm, preferably less than 20 μm or less than 15 μm, thereby making it possible to pass the liquid containing very fine residues of the other products of reaction (3). The filtered distillate, consisting of the powder of diboride of element M, is then calcined or dried, preferably in air, at a temperature above 80° C., preferably above 100° C. and / or preferably less than 300° C., preferably less than 200° C., preferably less than 150° C.
[0073] According to one possible embodiment, the liquid obtained from the filtration of the abovementioned suspension, which contains the products of reaction (3), apart from the diboride powder of element M, is thermally treated in the presence of water and a basic solution, thereby forming a hydrate of element R and an alkali hydroxide. This embodiment is represented by the formula A 2x R y O 5+x Preferably, this possibility is particularly advantageous when the element R is Al and the alkali A is sodium.
[0074] After milling the green powder, a finely divided final diboride powder of element M may be obtained, having a median diameter of 0.5-50 μm, high purity, micron-sized, and with a very small size distribution.
[0075] The final powder of the diboride of element M makes it possible to obtain, by sintering, ceramic sintered bodies having a total porosity of less than 7% by volume, while exhibiting a very low electrical resistivity, without the addition of transition metals, such as Ni, Fe or CO.
[0076] The final powder obtained according to the method of the invention also makes it possible to obtain sintered ceramic bodies in the form of parts, without deformation during sintering and without shrinkage cracks, having at least one dimension exceeding 5 cm in all dimensions.
[0077] The powder material according to the invention has an electrical resistivity, measured at 25° C. and atmospheric pressure, of less than 0.2 μΩ·m.
[0078] The electrical resistivity can be measured according to the Van der Pauw method at four points on a sample with a diameter of 20-30 mm and a thickness of 2.5 mm. The samples were obtained by pressing a mixture of the above powders with 0.25% by weight of a pressing additive (PVA) and 4.75% by weight of deionized water relative to the weight of the M diboride powder, thereby forming a cylinder with a diameter of 30 mm and a thickness of 10 mm, cold pressed under a pressure of 100 bar. After demolding, each cylinder was dried at 110° C. for 24 hours and then pressurelessly fired at a temperature of 1850° C. for 12 hours in argon.
[0079] The method for producing a sintered ceramic body using the powder according to the invention comprises in particular the following steps: (a) generating a starting feedstock comprising: - a diboride powder of element M according to the invention, where M is a chemical element belonging to group 4 of the periodic table, in particular a TiB2 powder, or a mixture of such powders, comprising said powder and one or more sintered powders, in particular selected from aluminium diboride, magnesium diboride, tungsten pentaboride, calcium hexaboride, silicon hexaboride, optionally zirconium diboride powders in the case of M=Ti or Hf, the purity of said MB2 powder being greater than 95% by weight, preferably greater than 98% by weight, said MB2 powder preferably representing at least 90% by weight of the total mass of the feedstock. an aqueous solvent, in particular deionized water, i. In the case of casting, it is less than 20% by weight of the total feedstock; ii. in the case of extrusion, less than 15% by weight of the total feedstock; iii. In the case of press molding, it is less than 10% of the total mass of the feedstock, preferably less than 7%; - preferably molding additives, such as binders, for example PVA (polyvinyl alcohol), plasticizers (for example polyethylene glycol), lubricants, etc. (b) forming the feedstock into the shape of a preform, preferably by pressing, extrusion, or casting; (c) Removal from the mold after solidification or drying; (d) optionally drying the preform, preferably to a residual moisture content of 0-0.5 wt.%; (e) The preform is loaded into a furnace and sintered under an inert atmosphere, preferably under argon or under vacuum, at a temperature preferably between 1600° C. and 2200° C., following a temperature ramp of preferably less than 20° C. / min, preferably less than 10° C. / min, which may be adjusted as a function of the mixing volume and the reactor power, as well as the duration of the plateau.
[0080] Any molding technique known to those skilled in the art can be applied as a function of the dimensions of the part to be made, as long as all precautions are taken to avoid contamination of the preform. Thus, casting in a gypsum mold can be adapted by using a graphite medium, or oil, between the mold and the preform to avoid excessive contact and wear of the mold due to mixing and thus contamination of the preform. These controlled precautions used by those skilled in the art can also be applied to the other steps of the method. Thus, the mold or matrix used to contain the preform during sintering will preferably be made of graphite.
[0081] The sintered ceramic bodies obtained from the powder according to the invention advantageously have an electrical resistivity, measured at 25° C. and atmospheric pressure, of less than 0.2 μΩ·m.
[0082] Hot pressing, hot isostatic pressing or SPS (spark plasma sintering) techniques are particularly suitable.
[0083] The following examples are for illustrative purposes only and are not intended to limit the scope of the invention in any described aspect. EXAMPLES
[0084] Example 1 (comparison):
[0085] The starting mixture was prepared by subjecting TiO2 in rutile form to a crystalline form, with a median diameter of D 50 Titanium oxide powder (purity 95%) with a median diameter of 10 μm, D 50 Powder of boron oxide B2O3 with a median diameter D equal to 15 μm 50 Carbon black powder having a particle size of 0.2 μm was used and the following respective mass proportions were prepared: 38.1% TiO2, 33.2% B2O3, and 28.7% C.
[0086] The mixed sample was placed in a graphite crucible with dimensions of 6 cm inner diameter, 8 cm outer diameter, and 8 cm height. The open crucible was placed in an induction furnace, whereby the flow rate in the oven was 1.25 L / min / m 3 Each was subjected to a heat treatment at 1600° C. in a flow of argon for a plateau duration of 2 hours.
[0087] The resulting synthesis mixture was milled for 3 minutes, thereby obtaining a powder with a median diameter of less than 10 microns (<10 μm).
[0088] Example 2 (according to the invention):
[0089] The starting mixture was treated with rutile crystalline crystalline zirconia (CuO) with a median diameter of 1.0 mm, as in the previous example, and a crystalline zirconia (CuO) with a median diameter of 1.0 mm, as in the previous example. 50 Titanium dioxide powder with a median diameter D of 10 μm, purity >99% by mass from Sigma Aldrich 50 Sodium tetraborate (Na2B4O7) powder with a median diameter D equal to 50 μm and a purity of more than 99% by mass from Alfa Aesar 50 Metallic aluminum powder with a median diameter D of 10 μm, purity >99% by mass from Sigma Aldrich 50 The mixtures were prepared using sodium oxide (Na2O) powder with a diameter of 50 μm according to the following respective mass proportions: 23.3%, 29.3%, 26.2%, and 21.2%. The mixed samples were placed in a graphite crucible of the same size as in the previous example. The open crucible was placed in a tube furnace, whereby it was subjected to a heat treatment at 800 °C with a temperature increase of 2 °C / min in the tube furnace, after which it was cooled to 1.25 L / min / m of the tube furnace vessel. 3 The step lasted for 2 hours in a furnace under a flow of argon.
[0090] The corresponding reaction balance is: 3TiO2+1.5Na2B4O7+10Al+3.5Na2O → TiB2+10NaAlO2 or as a function of the simple oxides TiO2, B2O3, and Na2O according to reaction (3): TiO2+B2O3+10 / 3Al+5 / 3Na2O → TiB2+10 / 3NaAlO2.
[0091] The resulting synthesis mixture was milled for 1 minute, thereby obtaining a powder with a median diameter of less than 30 microns (<30 μm). The resulting powder was mixed with deionized water according to the following ratio: 1 g powder to 50 ml water. The mixture was filtered through VWR 185 mm 12-15 μm paper to collect the titanium diboride particles. The distillate was dried at 110° C. to obtain the final dry titanium boride powder.
[0092] Example 3 (comparison):
[0093] This example differs from Example 2 in that the starting mixture was sodium hydroxide granules (NaOH content >99%) instead of sodium oxide powder. The respective weight ratios of titanium, sodium tetraborate, and aluminum metal powders, and sodium hydroxide granules were as follows: 21.9%, 27.6%, 24.7%, and 25.8%.
[0094] [Table 1]
[0095] The properties of the final powders obtained are shown in Table 2 below. Each powder was mixed with 0.25% pressing additive (PVA) and 4.75% by mass of deionized water relative to the mass of the powder, thereby cold pressing under a pressure of 100 bar to form a cylinder with a diameter of 30 mm and a thickness of 10 mm. After demolding, each cylinder was dried at 110°C for 24 hours and then pressureless sintered at a temperature of 1850°C for 12 hours in argon. The electrical resistivity of each example was measured at room temperature according to the Van der Pauw method at four points of the obtained sintered samples with a diameter of 20-30 mm and a thickness of 2.5 mm.
[0096] [Table 2]
[0097] These results of Example 2 in contrast to Comparative Example 1 show that by the method of the present invention it is possible to obtain very pure fine powders at lower synthesis temperatures without releasing CO. Comparison of Example 2 with Comparative Examples 1 and 3 shows that the raw powder according to the present invention is significantly less dispersed than that produced by the method of Comparative Example 3, especially based on aqueous sodium hydroxide (D 90 -D 10 ) / D 50 reference).
Claims
1. Diboride powder MB, where M is a chemical element belonging to group 4 of the periodic table 2 by reducing the oxide of M, comprising the steps of: - The following: (a) The oxide MO 2 A powder having a mass content of at least 95% (b) a powder containing boron oxide or a precursor of boron oxide, 2 O 3 a powder having a boron content of at least 30% represented by the formula: (c) a metal powder of at least one reducing element R, where R is selected from Al, Si, Ti, Zr, Hf, Y, Sc, lanthanides; and (d) an oxide powder of an alkali element A, containing at least 70% of A; 2 Oxide powder having a mass content of The MO 2 , B 2 O 3 , R, and A 2 and producing a feed mixture comprising, and preferably consisting of, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, MO 2 +B 2 O 3 +yR+8A 2 O → MB 2 +A 2x R y O 5+x (3) - heating said mixture in a vessel under a flow of noble gas at a temperature above 600°C and below 1500°C; and wherein the raw material mixture has the following characteristics: - the oxide MO 2 The median particle size of the powder is 1 to 100 μm; and the powder containing said boron oxide or boron oxide precursor has a median particle size of 5 to 200 μm; and - x is equal to or greater than 1, and - y is greater than 0.5; The method comprising:
2. 2. The diboride powder MB according to claim 1, wherein the hydroxyl mass content, calculated in the form of the mass of OH relative to the alkali metal, in the oxide powder of the alkali metal element A is less than 40%. 2 How to synthesize:
3. The boron oxide or the boron oxide precursor has the chemical formula NaBO 2 Sodium metaborate, of formula Na 2 B 4 O 7 or other borate salts, such as anhydrous borax of the formula Na 2 B 4 O 7 ・10H 2 Natural Borax of O, chemical formula Na 2 B 4 O 7 ・5H 2 O tincalconite, chemical formula Na 2 B 4 O 7 ・4H 2 O Kernite, chemical formula NaCaB 5 O 9 ・8H 2 O ulexite, chemical formula NaCaB 5 O 9 ・5H 2 Provertite of O, chemical formula H 3 B.O. 3 The diboride powder MB according to claim 1 or 2, which is selected from sassolite, boron nitride, etc. 2 How to synthesize:
4. The diboride powder MB according to claim 3, wherein the powder containing boron oxide is an anhydrous alkali borate powder, preferably an anhydrous sodium borate powder. 2 How to synthesize:
5. The oxide MO 2 The powder MB according to any one of claims 1 to 4, wherein the median particle size of the powder comprising the powder is more than 7 μm and / or less than 50 μm. 2 How to synthesize:
6. The powder MB according to any one of claims 1 to 5, wherein the powder containing boron oxide has a median particle size of more than 30 μm and / or less than 100 μm. 2 How to synthesize:
7. The median particle size of the powder containing boron oxide is 2 The powder MB according to any one of claims 1 to 6, wherein the ratio of the powder containing 2 How to synthesize:
8. Powder MB according to any one of claims 1 to 7, wherein the heating temperature in the container is higher than 700°C and / or lower than 1400°C. 2 How to synthesize:
9. Powder MB according to any one of claims 1 to 8, wherein the noble gas is selected from argon or helium. 2 How to synthesize:
10. Powder MB according to claim 9, wherein A is the element Na. 2 How to synthesize:
11. Powder MB according to claim 10, wherein R is the element Al and / or Si. 2 How to synthesize:
12. Powder MB according to any one of claims 1 to 11, in which M is the element Ti, A is the element Na and R is the element Al and / or Si. 2 How to synthesize:
13. Compound MB obtained according to any one of claims 1 to 12. 2 wherein M is selected from Ti, Zr, Hf, and has a median diameter of 0.5-50 μm and a chemical composition comprising the following elemental mass percentages: - elemental oxygen (O): less than 1.3%; - elemental carbon (C): less than 0.5%; - elemental nitrogen (N): less than 0.5%; - elemental sulfur (S): less than 400 ppm; elemental iron (Fe): less than 0.45%; elemental nickel (Ni): less than 0.4%; - elemental cobalt (Co): less than 0.4%; - the sum of the elements of alkali metals (Li+Na+K+Rb+Cs): less than 1%; - the sum of the elements of alkaline earth metals (Be+Mg+Ca+Sr+Ba): less than 1%; - content of element R in metallic form: less than 2%; R is preferably different from M, and R is at least one element selected from Al, Si, Ti, Zr, Hf, Y, Sc, lanthanides; The total of other elements is less than 2%.
14. The TiB according to claim 13 2 having a chemical composition in the following elemental mass percentages: Titanium (Ti): more than 68% and / or less than 72%; boron (B): more than 29% and / or less than 33%; - preferably less than 0.3% phosphorus (P); - metallic aluminum: less than 2%; - Metallic silicon: less than 1% Contains, powder.
15. MB according to any one of claims 13 and 14. 2 wherein the ratio of equivalent diameters of the particles of said powder (D 90 -D 10 ) / D 50 is less than 1.5, more preferably less than 1.
2.
16. A mixture comprising 90% by weight to 99.9% by weight of MB according to any one of claims 13 to 15. 2 and 0.1% to 10% by weight of one or more sintered powders selected from aluminium diboride, magnesium diboride, tungsten pentaboride, calcium hexaboride, silicon hexaboride, optionally zirconium diboride powders in the case M=Ti or Hf, preferably having a purity of more than 95% by weight.
17. A method for producing a ceramic sintered body, comprising the following steps: (a) The following: MB according to claims 13 to 15 2 or a mixture of powders according to claim 16, - aqueous solvents, in particular deionized water, - preferably molding additives, producing a starting feedstock comprising (b) forming the starting feedstock into the shape of a preform; (c) After solidification or drying, removing from the mold; (d) optionally drying the preform, preferably to a residual moisture content of 0-0.5 wt.%; (e) loading into a furnace and firing the preform under an inert atmosphere, preferably under argon atmosphere, or under vacuum, preferably at a temperature between 1600° C. and 2200° C.; A method comprising:
18. A ceramic sintered body obtainable by the method according to claim 17.
19. 19. Use of the ceramic sintered body according to claim 18 as all or part of a membrane, a shielding or wear-resistant coating, a covering or refractory block, an anode coating or block, or a cathode coating or block, a heat exchanger, a metal melting crucible, in particular for non-ferrous metals, a cutting tool.